Acute myeloid leukemia induced by MLL-ENL is cured by oncogene ablation despite acquisition of complex genetic abnormalities - Horton, Sarah J.; Walf-Vorderwülbecke, Vanessa; Chatters, Steve J.; Sebire, Neil J.; de Boer, Jasper; Williams, Owen (Blood, 2009)
Chromosomal translocations involving 11q23 are frequent in infant acute leukemia and give rise to the formation of MLL fusion genes. The mechanism of leukemic transformation by these fusions has been the subject of numerous investigations. However, the dependence of acute leukemia on MLL fusion activity in vivo and the efficacy of targeting this activity to eliminate disease have not been established. We have developed a model for conditional expression of MLL-ENL in hematopoietic progenitor cells, in which expression of the fusion oncogene is turned off by doxycycline. Conditionally immortalized myeloblast cells derived from these progenitors were found to induce leukemia in vivo. Leukemic cells isolated from primary recipient mice were shown to have acquired additional genetic abnormalities and, when transplanted into secondary recipients, induced leukemia with shortened latencies. However, the leukemic cells remained dependent on MLL-ENL expression in vitro and in vivo, and its ablation resulted in regression of established leukemias. This study demonstrates that even genetically complex leukemias can be reversed on inactivation of the initiating MLL fusion and has important implications for the design of novel leukemia therapies.